SOCIAL AND POLITICAL DIMENSIONS IN ISLAMIC STUDIES: AN ANALYSIS OF THE CONTEMPORARY RELEVANCE OF SHARIA VALUES - Husni, Hafizul; Zuhdiyah, Zuhdiyah; Maryamah, Maryamah (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
This study examines the social and political dimensions of Islam by analyzing the relevance of Sharia values within both historical and contemporary socio-political contexts, with particular attention to Southeast Asia. The research addresses two central questions: how have Islamic principles historically shaped governance, leadership ethics, and civic participation, and in what ways do these principles continue to influence contemporary political systems in Muslim-majority societies. Employing a qualitative, literature-based approach, the study explores key Islamic concepts such as shura (consultation), social justice, and public accountability, tracing their historical foundations while assessing their adaptation within modern democratic and constitutional frameworks. The findings demonstrate that Islam functions not only as a theological system but also as a dynamic socio-political and moral framework that informs ethical governance and civic engagement in the present era. By distinguishing clearly between historical precedents and contemporary applications, this study contributes to the broader literature on Islam and politics by highlighting the adaptive capacity of Sharia values in responding to modern governance challenges, including pluralism, accountability, and social justice.